Upregulation of High Mobility Group Box 1 May Contribute to the Pathogenesis of Biliary Atresia - Ye, Chun Jing; Wang, Jiang; Yang, Yi Fan; Shen, Zhen; Chen, Gong; Huang, Yan Lei; Zheng, Yi Jie; Dong, Rui; Zheng, Shan (European Journal of Pediatric Surgery, 2019)
Introduction Biliary atresia (BA) is a progressive inflammatory obstructive cholangiopathy in infants. High mobility group box 1 (HMGB1) is known to play an important role as a late mediator of inflammation. However, it is not clear whether HMGB1 levels are of clinical significance in patients with BA. The aim of this study was to determine correlations between serum HMGB1 levels and the clinicopathologic features of BA.Materials and Methods Serum samples were collected from 19 infants with BA, 7 infants with anicteric choledochal cysts (CC) and normal liver function, and 8 healthy controls. Serum HMGB1 levels were measured with an enzyme-linked immunosorbent assay. Routine liver function tests were performed on serum samples. Quantitative real-time polymerase chain reaction and western blot analyses were used to detect HMGB1 expression in BA liver biopsy tissues. Localization of HMGB1 expression in the hepatic lobule was determined by immunohistochemical analysis.Results HMGB1 levels in serum collected from BA infants were significantly elevated compared with CC and healthy control patients. Furthermore, elevated serum levels of HMGB1 in BA infants positively correlated with gamma-glutamyl transferase levels. HMGB1 messenger ribonucleic acid and protein expression levels were upregulated in BA liver biopsy tissues compared with CC patients. Immunohistochemical analysis also revealed increased positive immunostaining for HMGB1 in BA liver tissues as compared with CC tissues.Conclusion HMGB1 may play a crucial role in the pathogenesis of BA. Additionally, the correlation of serum HMGB1 levels with gamma-glutamyl transferase levels may provide a novel marker for the diagnosis of BA.
Keywords: biliary atresia; high mobility group box 1; biomarker